Improvement of engineering student’s learning outcomes in high schools using adaptive educational hypermedia system - Sumarlin, Sumarlin; Setyosari, Punaji; Ulfa, Saida; Degeng, Made Dunanda Kartika (International Journal of Evaluation and Research in Education (IJERE), 2024)
This was a research and development (R&D) which aims to develop adaptive educational hypermedia system (AEHS) learning media. The use of AEHS based on learning style in supporting the online learning process is considered very effective for use by engineering students because it can be accessed via mobile devices which can make it easier for students to learn and has an effect on increasing learning outcomes, this is supported by several inputs from experts through expert learning design tests, learning instrument experts, learning media experts and learning outcome measurement experts with the assessment results included in the very good category. The participants in this study were informatics engineering students, totaling 100 students. Small group tests were conducted for participants and obtained a gain score of 0.735 included in the 'high' category. The pretest and posttest have been carried out and the results show that the average posttest score is greater than the pretest value. A comparison between the use of AEHS developed with web-based learning was carried out and it can be concluded that the use of AEHS based on learning styles further improves student learning outcomes in informatics engineering compared to web-based learning.